206. Respiratory Viral Testing Is Associated with Lower Frequency of Antibiotic Prescribing for Acute Upper Respiratory Infections at a Large Ambulatory Cancer Center. (26th November 2018) - Krantz, Elizabeth M; Stohs, Erica; Sweet, Ania; Zier, Jacqlynn; Marquis, Sara; Klaassen, John; Pergam, Steven; Liu, Catherine
Abstract: Background: Inappropriate outpatient antibiotic prescribing for acute upper respiratory infections (URIs) is a high priority target for antimicrobial stewardship and has not been described for cancer patients. The goal of this study was to characterize patterns of and factors associated with antibiotic prescribing among ambulatory oncology patients with URIs. Methods: We selected outpatients >18 years old seen at an ambulatory cancer center with ICD-10 diagnosis code consistent with URI from October 1, 2015 to September 30, 2016 for chart review. Patients without documented active URI symptoms or with lower tract infection at the first clinical encounter for the URI (day 0) were excluded. We obtained demographic, clinical, antimicrobial prescribing and viral testing data for days 0–14. We used generalized estimating equations to test for associations of baseline factors with a ≥1 antibiotic prescription for URI while accounting for correlation among patients seen by the same provider. Results: Of the 341 charts reviewed, 251 (74%) patients, seen by 99 providers were eligible for analysis. A total of 162/251 (65%) had an underlying hematologic malignancy or disorder; of those, 51% had a prior hematopoietic cell transplant. Eighty-four (33%) received ≥1 antibiotic prescription for URI with 63% ordered on day 0. Azithromycin (47%) and fluoroquinolones (25%) were most often prescribed. One hundred thirteen (45%) patients had respiratory viral testing performed; 85 (75%) tested positive (Figure 1). Both antibiotic prescribing ( P = 0.005) and viral testing ( P < 0.001) varied by clinical service (Figure 2). Viral testing on day 0 was associated with lower risk of antibiotic prescribing while sputum production or chest congestion was associated with higher risk of antibiotic prescribing (Figure 3). Conclusion: Antibiotics were prescribed in one in three oncology outpatients with URI, although viral etiologies were identified in most who were tested. Respiratory viral testing was associated with reduced antibiotic prescribing though collinearity between clinical service and viral testing limited our ability to separate these effects on antibiotic prescribing. It is important to further explore the role of viral testing in antibiotic prescribing for URI in outpatient oncology settings. Disclosures: All authors: No reported disclosures.